Faktor -faktor yang Memengaruhi Internet Gaming Disorder pada Remaja di Era Teknologi Modern: Literature Review - Ida Bagus Danandinatha Adhyaksa; Tience Debora Valentina (Humanitas (Jurnal Psikologi), 2023)
In the era of modern technology, the development of technology has a great impact on its use. Teenagers use the internet to quickly access information, entertainment media, and play online games. Compulsive and unruly behavior of playing online games in such a way will cause addiction to online games or what is often called Internet Gaming Disorder. The purpose of this study is to see what factors can support or influence the occurrence of Internet Gaming Disorder in adolescents. A descriptive literature review was conducted on 10 articles using quantitative research with diverse sampling methods and adolescent respondents. The results of a literature study show that there are factors that affect internet gaming disorder in adolescents, including gaming motives, social anxiety, motivation and social support, loneliness and affiliated needs, sensation seeking, parental parenting, attention problems, stress levels, internet escapism, self-control.